Dating the earliest human occupation of Western Europe: New evidence from the fluvial terrace system of the Somme basin (Northern France). (3rd June 2015) - Antoine, P.; Moncel, M.-H.; Locht, J.-L.; Limondin-Lozouet, N.; Auguste, P.; Stoetzel, E.; Dabkowski, J.; Voinchet, P.; Bahain, J.-J.; Falgueres, C.
Abstract: Dating the earliest human occupation of Western Europe and reconstructing its relations with climatic and environmental constrains is becoming a central question, especially with the discovery of Palaeolithic artefacts allocated to the Early Pleistocene in south-east Britain and in Central France. In this context, the Quaternary sequences of the Somme basin, where is located the type-site of the Acheulean, is a key area. Research undertaken for more than 20 years on both fluvial and loess sequences of the Somme basin provide a unique dataset for the study of the relations between human occupations and environmental variations. Studies have been based on an interdisciplinary approach combining sedimentology, palaeontology and geochronology (U-series, ESR and ESR/U-series). Meanwhile, the palaeoenvironmental interpretation of Pleistocene sequences containing Palaeolithic levels has been refined with biological proxies and sedimentological data obtained on both loess and fluvial sequences. Our data have highlighted the impact of the 100 ky cycles on terraces formation since ±1 Ma, and the fluvial terraces system of the Somme basin has become a reference model for the study of the response of fluvial systems to Milankovich cycles in areas characterised by slow continuous uplift. Compilation of the whole results from modern archaeological excavations within this chronoclimatic reference system show that human occupation of this area has been discontinuous and highly influenced by climatic and environmental factors. In the Somme terraces system in situ Acheulean settlements where dated to early MIS 12 at ±450 ka in the 1990s, but new field discoveries allow to increase significantly the age of the oldest human occupation (Early Middle Pleistocene). The first one (Amiens "Rue du Manège" 2007) is dated at ±550 ka using ESR and terrace stratigraphy. The newest findings have been done in 2011–2013 in Abbeville (Carrière Carpentier), where mammal assemblages show that calcareous fluvial deposits have been deposited in an interglacial environment. On the basis of terrace stratigraphy, ESR-quartz dating, and biostratigraphic data, these fluvial deposits are allocated to MIS 15. Handaxes discovered at the base of the slope deposits, directly overlying the fluvial sequence, can be, as a first hypothesis, allocated to MIS 14. They are thus due to Homo heidelbergensis according to the age of the eponymous Mauer site in Germany. Consequently, in the state of knowledge, the "Rue du Manège" and Carrière Carpentier findings represent the oldest in situ evidence of the hominid occupation in the terrace record of Northern France.